2020
DOI: 10.3390/diagnostics10100782
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reciprocally Dysregulated miRNAs in Eutopic Endometrium Is a Promising Approach for Low Invasive Diagnostics of Adenomyosis

Abstract: Endometriosis is a chronic disease characterized by the growth of endometrial tissue outside of the uterine cavity. Endometriosis affects up to 10% of women of reproductive age and has great social impact. The diagnostics of endometriosis are based on clinical appearance, ultrasound, and magnetic resonance imaging (MRI); however, a diagnosis is frequently hampered by the absence of objective criteria. Adenomyosis (AM) is a particular type of endometriosis wherein the spread of the ectopic endometrial gland is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…Eutopic endometrium of patients with AD exhibits reciprocally dysregulated miRNAs such as upregulated miR-191, the analysis of which may be a promising low-invasive method for efficient diagnosis of AD ( 20 ). In addition, miRNAs participate in lncRNA-mediated AD progression by serving as the downstream targets of lncRNAs ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eutopic endometrium of patients with AD exhibits reciprocally dysregulated miRNAs such as upregulated miR-191, the analysis of which may be a promising low-invasive method for efficient diagnosis of AD ( 20 ). In addition, miRNAs participate in lncRNA-mediated AD progression by serving as the downstream targets of lncRNAs ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, at only ~22 nucleotides in length and also classified as ncRNAs, microRNAs (miRNAs or miRs) have been discovered to act as a downstream mechanism of lncRNA-mediated changes in processes of ESCs during AD progression ( 13 ). Among them, miR-191 is notably dysregulated in the endometrium tissues of patients with AD ( 20 ). Therefore, identifying downstream miRNAs of lncRNAs that regulate AD is key.…”
Section: Introductionmentioning
confidence: 99%
“…Анализ прогностической значимости реципрокных пар микроРНК. Феномен сочетанных и разнонаправленных (реципрокных) изменений экспрессии 2 молекул ми-кроРНК в процессе развития онкологических заболеваний был описан ранее [17,38,39]. В ряде исследований было показано, что анализ соотношения концентраций 2 молекул микроРНК, для которых характерны разнонаправленные опухольассоциированные изменения экспрессионной активности, может иметь высокий диагностический потенциал.…”
Section: оригинальные статьиunclassified
“…Noncoding RNAs, containing microRNAs (miRNAs), long noncoding RNAs, and circular RNAs (circRNAs), are pivotal molecules in regulating the pathology of human diseases [11]. Accruing articles have indicated that miRNAs and long noncoding RNAs exerted pivotal functions in adenomyosis development [12][13][14]. Nevertheless, the roles of circRNAs in adenomyosis progression have been rarely studied.…”
Section: Introductionmentioning
confidence: 99%